Changes in Anthropometric Measures of Wellbeing in Korea from 1945 to 1977: Evidence from Korean Military Records - Lee, Chulhee (KDI School of Public Policy and Management, 2020)
Although it is widely acknowledged that the rapid economic growth in South Korea during the second half of the twentieth century improved the standards of living of the population, it is not fully understood how the living conditions in South Korea changed over time, and what are the major factors that produced the changes. Research on these issues is often seriously limited by shortage of appropriate data, especially for the period between 1945 and 1960. The present study attempts to overcome the limitations of currently available data on standards of living by analyzing a newly collected sample of Korean military records. Using these sources, we have investigated how biological indices of standards of living, such as height, weight, and body-mass-index (BMI) changed across birth cohorts born between 1946 and 1957. We also examined how changes in anthropometric measures differed by province of residence, father’s occupation, and own education. The mean height of 20-year-old males in South Korea slightly declined from the 1946 birth cohort to those born in 1951, before it rapidly increased across cohorts. As for the average weight, a sharp decline and recovery of weights around the first two years of the Korean War (1950 and 1951) is observed. These results suggest that the Korean War likely affected significantly the anthropometric measures of the birth cohorts who experienced the war in utero or in early childhood. There were considerably large variations across provinces in the patterns of changes in anthropometric measures as well as the levels of the measures. Generally speaking, men who resided in Seoul and other metropolitan cities (Busan, Daegu, Gwangju, Daejeon, and Ulsan) are taller than those from non-metropolitan provinces. In contrast, men from the majority of non-metropolitan provinces are significantly shorter than those from Seoul. In sharp contrast to the results for height, urban disadvantages in weight are observed. The results of regression analyses show that the observed provincial differences in anthropometric measures do not disappear even if father’s occupation and own education are controlled. Consistent with the urban advantages found in provincial differences in height, the children of farmers turned out to be shorter that the offspring of non-farmers. Own education is positively associated with height and weight. These results suggest that the observed regional differences in the level and trend of biological standard of living in South Korea prior to the mid-1970s were probably produced by provincial differences in socioeconomic and environmental characteristics. It will be the next step of this research project to explore what are the major factors that produced the secular changes and regional differences in biological standards of living in South Korea prior to the 1970s. We are currently in the process of collecting and inputting county-level variables that are believed to be associated with net nutritional status of the population, including agricultural production, urbanization, and industrialization. We plan to conduct additional analyses by adding these factors on local environments to the variables on personal characteristics utilized in this study. We anticipate that the results of these further analyses will allow us to determine what socioeconomic changes or policy measures were the major contributors to the improvements of wellbeing of the Korean people.